ANALYSIS THE EFFECT OF CRUDE PALM OIL EXPORTS ON THE INDONESIAN ECONOMY - Belinda Zayanti; Zhafira Audreya Kanisya; Nur Azzahara; Wiwik; Wansa; M. Ilham Manches (CV. Era Digital Nusantara, 2023)
The purpose of this study is to find out how significant the export of Crude Palm Oil is in influencing the Indonesian economy and how much the contribution of Crude Palm Oilexports is in boosting the economy of the Republic of Indonesia. This study uses the library study method, because literature sources are obtained from journals, research reports, information from social media, statistical data and other sources. The approach in this study uses a quantitative descriptive. The fact is that Crude Palm Oil is a sector that greatly contributes to increasing exports in the country's economic development.